The effect of vacancy defects on the adsorption of methane on calcite 104 surface - G.R. Berdiyorov (7170563) (2021)
Density functional theory calculations are used to study the effect of vacancy defects (ionic Ca and charge neutral CO3) on the adsorption properties of CH4 molecule on different calcite surfaces. Both types of vacancy defect results in strong adsorption of the gas molecules as compared to defect-free sample. For example, for the 104 surface of the material the methane molecules gets adsorbed stronger by 63.6% and 24.4% for Ca and CO3 vacancy defects, respectively. Such enhanced adsorption of the CH4 molecule due to the presence of the vacancy defects is also obtained for the other surface symmetries. Electronic structure calculations show that the latter is due to the orbital-overlap/hybridization between the organic molecules and the substrate. Adsorption capacity of the calcite also increases due to the presence of the defect. Vacancy defects also create energy barriers for the migration of CH4 on the surface of calcite as revealed in our nudged elastic band calculations. The effect on the CH4 adsorption and migration becomes more pronounced in the case of Ca vacancy defect. These findings could be of practical importance for, e.g., estimating ultimate gas recovery. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2021.08.091